Pengaruh Marketing Mix Terhadap Kepuasan Konsumen Pada CV Froston Bag Kota Tangerang - Atikah Hulwah Ramadhania; Rahadyan Tajuddien (JURNAL ILMIAH NUSANTARA, 2025)
The purpose of this study was to determine how the 4C Marketing mix affects customer satisfaction at CV Froston Bag Tangerang City both partially and simultaneously. The sampling technique used was the Slovin technique with a sample of 90 respondents. Data analysis using data instrument test, classical assumption test, hypothesis testing. The results of the research variable customer value determination value of 53.1% while the remaining 46.9% is influenced by other factors. Hypothesis testing obtained t value> t table or (9.973> 1.987). Thus H0 is rejected and Ha is accepted, meaning that there is a positive and significant influence between customer value on customer satisfaction. Cost has a positive and significant effect on customer satisfaction with a determination value of 40.8% while the remaining 59.2% is influenced by other factors. Hypothesis testing obtained t value> t table or (7.783> 1.987). Thus H0 is rejected and Ha is accepted, meaning that there is a positive and significant influence between cost on customer satisfaction. Convenience has a positive and significant effect on customer satisfaction with a determination value of 64.8% while the remaining 35.2% is influenced by other factors. Hypothesis testing obtained t value> t table or (12.730> 1.987). Thus H0 is rejected and Ha is accepted, meaning that there is a positive and significant influence between convenience on customer satisfaction. Communication has a positive effect on customer satisfaction with a determination value of 28.8% while the remaining 71.2% is influenced by other factors. Hypothesis testing obtained t value> t table or (5.966> 1.987). Thus H0 is rejected and Ha is accepted, meaning that there is a positive and significant influence between communication on customer satisfaction. Marketing mix 4C has a positive and significant effect on customer satisfaction simultaneously with a determination value of 74.9% while the remaining 25.1% is influenced by other factors. Hypothesis testing obtained the value of f count> f table or (63.579> 3.101). Thus H0 is rejected and Ha is accepted, meaning that there is a simultaneous positive and significant influence between the 4C marketing mix on customer satisfaction at C Froston Bag Tangerang City